Influence of osmotic stress on the profile and gene expression of surface layer proteins in Lactobacillus acidophilus ATCC 4356 - Palomino, Maria Mercedes (2016)
In this work, we studied the role of surface layer (S-layer) proteins in the adaptation of Lactobacillus acidophilus ATCC 4356 to the osmotic stress generated by high salt. The amounts of the predominant and the auxiliary S-layer proteins SlpA and SlpX were strongly influenced by the growth phase and high-salt conditions (0.6 M NaCl). Changes in gene expression were also observed as the mRNAs of the slpA and slpX genes increased related to the growth phase and presence of high salt. A growth stage-dependent modification on the S-layer protein profile in response to NaCl was observed: while in control conditions, the auxiliary SlpX protein represented less than 10 % of the total S-layer protein, in high-salt conditions, it increased to almost 40 % in the stationary phase. The increase in S-layer protein synthesis in the stress condition could be a consequence of or a way to counteract the fragility of the cell wall, since a decrease in the cell wall thickness and envelope components (peptidoglycan layer and lipoteichoic acid content) was observed in L. acidophilus when compared to a non-S-layer-producing species such as Lactobacillus casei. Also, the stationary phase and growth in high-salt medium resulted in increased release of S-layer proteins to the supernatant medium. Overall, these findings suggest that pre-growth in high-salt conditions would result in an advantage for the probiotic nature of L. acidophilus ATCC 4356 as the increased amount and release of the S-layer might be appropriate for its antimicrobial capacity.